2019
DOI: 10.5644/ama2006-124.269
|View full text |Cite
|
Sign up to set email alerts
|

Neuroenhancing Substances Use, Exam Anxiety and Academic Performance in Bosnian-Herzegovinian Firstyear University Students

Abstract: Objective. The aim of this study was to assess the relationship between the use of neuroenhancing substances, exam anxiety and academic performance among first-year Bosnian-Herzegovinian (BH) university students. Methods. In a cross-sectional study, an ad hoc questionnaire was delivered to a sample of BH first-year university students. The following data were collected: socio-demographic features, consumption of neuroenchancing substances, the Westside Test Anxiety Scale (WTAS) and academic performance. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A study at Universities in Trnava reported better mood, more concentration, increased physical activity and hyperactivity in respondents after the energy drinks consumption, while sleep suppression was reported by the majority [ 42 ]. However, consumption of coffee and energy drinks, for the purpose of neuroenhancement was found to be increased during the week before the exams among Bosnian-Herzegovinian university students and was correlated with exam stress level [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study at Universities in Trnava reported better mood, more concentration, increased physical activity and hyperactivity in respondents after the energy drinks consumption, while sleep suppression was reported by the majority [ 42 ]. However, consumption of coffee and energy drinks, for the purpose of neuroenhancement was found to be increased during the week before the exams among Bosnian-Herzegovinian university students and was correlated with exam stress level [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies separate marijuana or cannabis use from each other IDU [ 65 , 69 ]. Others refer to a mesh of terms e.g., neuroenhancing substances (could include coffee, energy drinks, nicotine, alcohol) or psycostimulants [ 70 ]; illicit stimulants (amphetamines, Fenethylline, Ritalin, Concerta, Dexedrine, Adderall, Vyvanse) [ 71 ]; nonmedical attention deficit hyperactivity disorder (ADHD) medication [ 72 ]; illicit substances (including cocaine, designer drugs, and nonmedical use of prescription stimulants and opioids) [ 73 ]; illicit drug use, and misuse of prescription stimulants, sedatives, and opioids [ 74 ]; hallucinogen use [ 75 ]; smart drugs (aka cognitive enhancers, prescription drugs taken, either without a prescription or at a dose exceeding that which is prescribed) [ 76 , 77 ]; street drugs vs. prescription drugs [ 78 ]; or nonmedical use of prescription stimulants [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pekrun et al (2011) showed that students' motivation, control, use of learning strategies, value appraisals, academic performance and self-regulation of learning are directly linked and connected to their emotions regarding their achievements (Pekrun et al 2011). Significant negative emotions, such as shame, anger and anxiety, have very negative effects on their performance, as expected (Hancock 2001;Kusturica et al 2019;Pekrun et al 2011). In addition, the educational engagement and effective learning in general are directly affected by the disadvantages of long-term distancing and isolation (Carlson 2020).…”
Section: Students' Mental Health and Emotions During Covid-19mentioning
confidence: 96%